(untitled) (Experimental biology, 2016)
Biomass growth and biosynthesis of biologically active substances in the strains Streptomyces candidus IMV 37 and Streptomyces canofumeus IMV 541 formulating a preparation for plant cultivation have been studied in 10 organic and synthetic culture media. Considerable effect of medium composition on the growth of Streptomyces strains and formation rate of biologically active substances was shown. The optimal biomass growth of studied Streptomyces strains provide organic medium with soy flour. Medium No. 8 with oat flour is the most optimal for the synthesis of both antifungal antibiotic, and plant growth-stimulating substances. Medium No. 8 supports high-level biomass accumulation (45.8 g/L) of the strain Streptomyces canofumeus IMV 541, and strong antifungal activity of the culture fluid (zone diameter of growth inhibition of the test organisms is within 31-32 mm) and biomass extracts (36 mm). Culture fluid of the strain Streptomyces candidus IMV 37 obtained in the medium No. 8 increases the germination energy of wheat seeds by 26.6%, laboratory germination capacity by 20.0%, length of sprouts 2.2 times, root length 2.0 times, and plant wet weight 1.9 times.